Profiling complex word usage in the speech of preschool children: Frequency patterns and transparency characteristics. Issue 6 (December 2019) - Laws, Jacqueline
This corpus-based study provides a baseline of complex word usage patterns in the spontaneous speech of English preschool children to ascertain the characteristics of their derivative vocabulary before literacy development affects language skills. Frequencies of suffixed derivatives produced by ( N = 243) children aged 2–5 and their caregivers were extracted for 58 suffix variants, yielding 558 types from the former and 1, 364 from the latter. Between the youngest and oldest groups, 11 suffix categories increased significantly in type frequency, compared with 22 in the caregiver dataset. All derivative types were classified for transparency of meaning and simplicity of form on a five-point analysability scale. Around 59% of both the child and caregiver derivative vocabulary sets were classified as transparent regardless of age, suggesting that the potential analysability of the preschool child's input remains surprisingly invariant over time. The study provides baseline data for future studies on the development of morphological awareness in English- speaking schoolchildren.